Frontline nurses' burnout, anxiety, depression, and fear statuses and their associated factors during the COVID-19 outbreak in Wuhan, China: A large-scale cross-sectional study. (July 2020) - Hu, Deying; Kong, Yue; Li, Wengang; Han, Qiuying; Zhang, Xin; Zhu, Li Xia; Wan, Su Wei; Liu, Zuofeng; Shen, Qu; Yang, Jingqiu; He, Hong-Gu; Zhu, Jiemin
Abstract: Background: During the Coronavirus Disease 2019 (COVID-19) pandemic, frontline nurses face enormous mental health challenges. Epidemiological data on the mental health statuses of frontline nurses are still limited. The aim of this study was to examine mental health (burnout, anxiety, depression, and fear) and their associated factors among frontline nurses who were caring for COVID-19 patients in Wuhan, China. Methods: A large-scale cross-sectional, descriptive, correlational study design was used. A total of 2, 014 eligible frontline nurses from two hospitals in Wuhan, China, participated in the study. Besides sociodemographic and background data, a set of valid and reliable instruments were used to measure outcomes of burnout, anxiety, depression, fear, skin lesion, self-efficacy, resilience, and social support via the online survey in February 2020. Findings: On average, the participants had a moderate level of burnout and a high level of fear. About half of the nurses reported moderate and high work burnout, as shown in emotional exhaustion ( n  = 1, 218, 60.5%), depersonalization ( n  = 853, 42.3%), and personal accomplishment ( n  = 1, 219, 60.6%). The findings showed that 288 (14.3%), 217 (10.7%), and 1, 837 (91.2%) nurses reported moderate and high levels of anxiety, depression, and fear, respectively. The majority of the nurses ( n  = 1, 910, 94.8%) had one or more skin lesions, and 1, 950 (96.8%) nurses expressed their frontline work willingness. Mental health outcomes were statistically positively correlated with skin lesion and negatively correlated with self-efficacy, resilience, social support, and frontline work willingness. Interpretation: The frontline nurses experienced a variety of mental health challenges, especially burnout and fear, which warrant attention and support from policymakers. Future interventions at the national and organisational levels are needed to improve mental health during this pandemic by preventing and managing skin lesions, building self-efficacy and resilience, providing sufficient social support, and ensuring frontline work willingness.